2005
DOI: 10.1021/np040199j
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Aldose Reductase Inhibitory Effects of Bromophenols from the Red Alga Symphyocladia latiuscula

Abstract: Three new bromophenols, 2,2',3,6,6'-pentabromo-3',4,4',5-tetrahydroxydibenzyl ether (1), bis(2,3,6-tribromo-4,5-dihydroxyphenyl)methane (2), and 2,2',3,5',6-pentabromo-3',4,4',5-tetrahydroxydiphenylmethane (3), were isolated from the red alga Symphyocladia latiuscula. Two bromophenols, 2,3,6-tribromo-4,5-dihydroxymethylbenzene (4) and 2,3,6-tribromo-4,5-dihydroxybenzaldehyde (5), were also reported for the first time as natural products. Their structures were elucidated on the basis of chemical and spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 17 publications
2
68
0
Order By: Relevance
“…It has been reported that naturally occurring bromophenol 1 shows enzyme inhibition 3 , cytotoxicity 4 , feeding deterrent 5 , anti-microbial 6 , anti-cancer 7 and anti-oxidant 8 activities. Aldose reductase 9 and carbonic anhydrase 10 inhibitory properties of natural products 2-3 have also been noted ( Figure 1). The high-density lipoprotein associated serum esterase, paraoxonase (arylesterase, EC 3.1.8.1, PON1) is a key enzyme for protection against atherosclerosis in metabolism.…”
Section: Introductionmentioning
confidence: 81%
“…It has been reported that naturally occurring bromophenol 1 shows enzyme inhibition 3 , cytotoxicity 4 , feeding deterrent 5 , anti-microbial 6 , anti-cancer 7 and anti-oxidant 8 activities. Aldose reductase 9 and carbonic anhydrase 10 inhibitory properties of natural products 2-3 have also been noted ( Figure 1). The high-density lipoprotein associated serum esterase, paraoxonase (arylesterase, EC 3.1.8.1, PON1) is a key enzyme for protection against atherosclerosis in metabolism.…”
Section: Introductionmentioning
confidence: 81%
“…389 Bromophenols 633−634, 659−660, and 676 exhibited significant aldose reductase inhibitory activity with IC 50 values ranging from 0.11 to 1.15 μg/mL, and the effect was similar to (633) or higher than (634, 659−660, and 676) that of the positive control (quercetin). 373 The bromophenols vidalols A (664) and B (685) are antiinflammatory agents that act through inhibition of phospholipase A 2 , causing 96% inactivation at 1.6 μg/mL. 386 However, it was difficult to maintain the purity of vidalols A and B during the bioassay, so it was not clear whether the inhibitory activity was caused by the compounds themselves or by degradation products thereof.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Of these natural compounds, 5,5′-methylenebis(3,4-dibromobenzene-1,2-diol) (1) and 3,4-dibromo-5-(2-bromo-3,4-dihydroxy-6-(methoxymethyl)benzyl)benzene-1,2-diol (2) exhibit enzyme inhibition, e.g. isocitrate lyase 3 cytotoxicity 4 , feeding deterrent 5 , and microbial 6,7 activities, while 3,4,6-tribromo-5-(2,5-dibromo-3,4-dihydroxybenzyl) benzene-1,2-diol (3) and 5,5′-methylenebis(3,4,6-tribromo-benzene-1,2-diol) (4) exhibit significant aldose reductase inhibitory activity 8 . Additionally, it was reported that bromophenol 1 is an inhibitor of protein tyrosine phosphatase 9 .…”
Section: Introductionmentioning
confidence: 99%